Strengthening Government Apparatus for the Success of Technology-Based Local Finance Information Systems (SIKD) - Rahayu Indriasari; Made Sudarma; Rosidi Rosidi; Endang Mardiati; Fibriyani Nur Khairin (Journal of Economics, Business, and Accountancy Ventura, 2017)
Local financial management improvements needs to be realized for good governance. Regulation No. 17 of 2003 requires regional governments to better manage their finances through technology based Local Finance Information Systems (SIKD). In practice, it often causes behavioral problems because it leads to changes in the system in a short time by claiming to gain a better system that complies with the financial administration system in Indonesia. Thus, the government has to pay attention to their apparatus. This study tries to find out factors for strengthening the finance staff for implementing technology-based SIKD. It used a phenomenological approach and the data were collected through observation, in-depth interview, and document analysis. Informants in this study are those who directly involved in technology-based SIKD, finance staff, and policy makers. It shows that there are three important factors for the success of technology-based SIKD. Firstly, the staff’s commitment to self- integrity. Secondly, ethics and morality for staff’s building character, and thirdly, improve the government apparatus’ capacity. In conclusion, the government should be proactive in improving the human resources quality for implementing technology-based SIKD, through socialization or training. Results of this study suggest that regional government regulates human resource development for the successful implementation of technology-based SIKD.